Importance of Judicial Activism to Ensure Transparency in Pakistan: A Case Study on Privatization of Pakistan Steel Mills Case 2006 - Waseem, Muhammad Aslam; Hussain, Shahzad (Journal of History Culture and Art Research, 2019)
This case study analyzes the attempt of the Government to privatize the Pakistan Steel Mills, after it had been revamped and had started generating profit. There were many irregularities in this case with respect to the actual decision to privatize, valuation of the assets as the land and other assets were not included, pre-qualification of the highest bidder, the final setting of the share price, and even undue concessions were provided to materialize the deal. Through this landmark judgment, the Supreme Court of Pakistan directed the Government to stop the process of privatization of a prime asset of Pakistan. The Court intervened only to the extent of applicability of the relevant rules regarding the privatization and tried to refrain from interference in the policy-making authority of the Government.